Enhancing Physics Learning Through Virtual Experiments: Analyzing Parabolic Motion and Maximum Height Using Tracker Software - Putri, Alfina Syifaaini; Agustina, Rinka Refat (Yayasan Darussalam Bengkulu, 2023)
The rapid development of digital technology has opened new opportunities for integrating virtual experiments into physics education, particularly during periods when face-to-face learning is limited. This study aimed to analyze projectile motion by determining the maximum height (Hmax) of a ball through a virtual experiment using Tracker software. The research employed a quantitative descriptive experimental design in which video analysis was conducted to capture and model parabolic trajectories, followed by calculations of maximum height and relative error. Data were obtained through repeated trials, and the results demonstrated that the measured trajectories were consistent with the theoretical model of parabolic motion. The experimental findings showed that the calculated Hmax values closely approximated theoretical predictions, with small relative errors confirming the reliability of the software in simulating motion. These results indicate that Tracker software is not only a powerful visualization tool but also a valid quantitative platform that supports students in linking theory with practice, analyzing real-world phenomena, and understanding the importance of error analysis in physics. The implication of this study is that integrating Tracker into physics instruction can enhance students’ conceptual understanding, scientific literacy, and analytical skills, while providing a cost-effective alternative to conventional laboratories in both face-to-face and remote learning contexts.